STRATEGI PROTEKSI TRANSAKSI KASIR PADA CENTRAL FASHION STORE CABANG CIKUPA KABUPATEN TANGERANG - Slamet Soesanto; Tatyana Tatyana; Annisa Anggraeni (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
The Central Fashion Store is a retail company engaged in the sale of clothing, accessories, and footwear from children to adults. The sales process takes place every day during operating hours. Process cash and non-cash payment transactions. In the process of store operations, cashiers play an important role in serving consumers. The duties and responsibilities of the cashier at the Central Fashion Store have been carried out properly. However, it is undeniable that in practice problems can still occur that have the potential to harm shops, consumers and the cashiers themselves. Problems that occur such as the computer does not respond, the barcode is not registered, scanned the barcode twice, entered the nominal incorrectly, the purchase receipt was not printed, the EDC machine network connection was problematic, the EDC machine was damaged and the difference in cash. Actions taken to overcome problems that occur include waiting for the computer to respond again or transactions are carried out manually, registering barcodes to the warehouse, always being careful in entering data into the system, checking the printer then reprinting the receipt, replacing the EDC machine sim card, waiting for repairs from the bank and be careful in returning money to consumers